Condicionamento e qualidade de sementes de milho no sincronismo de florescimento em campo de produção de sementes híbridas - Timóteo, Tathiana Silva (2007)
The production of maize hybrid seeds depends on the synchronism of flowering between the two parental lines, which normally have different cycles. In the present study, the effect of priming on maize seeds, with different levels of quality on the physiological quality and enzyme activity of the seeds and on the flowering time and other agronomic parameters were analyzed. Experiments were carried out at the experimental area and in the Laboratories of Analyses and Seed Biotechnology of the Department of Agriculture, Federal University of Lavras. Seeds of two lines (43 and 57) of simple hybrid GNZ 2004 were used as source of vegetal material. Samples of each lot had accelerating aging, for 96 hours, by gerbox method, aiming to have different seed lots with distinct physiological quality. Having the divided lots, experiments were carried out. In the first experiment, high and low quality seeds were used, associated to the priming not, in water for 24 hours at 35ºc, being part of the seeds dried for 24 hours, just after priming, until 13% of water content. In the second experiment, high and low quality seeds were used, associated to the priming or not, in water for 24 hours and having or not the recommended split for the appropriated hybrid, which is 3 days, getting in total four treatments for each line. Experimental designs consisted of a randomized complete block in 4 repetitions. Each experimental plot was done by six lines of 4 meters each. Seedling emergence and plant height were measured. Percentage of seedling emergence in the field and plant height were measured when 50% and 100% of pollen release and the emission of stile-stigma occurred and moreover, by the date of no pollen release of male parent and receptivity of stigma-stile of female parent and by the date when the seeds were at stage ML 3 of development, for each treatment. It was concluded that the physiological quality and enzyme activity in seeds are affected by priming. Moreover, priming affected plant flowering, becoming a viable alternative to reduce splits, mainly when seeds with different level of quality are used.